Heat Rate Gap and Cost Analysis Due to Increase of Condenser Pressure in A 660 MW Combined Cycle Power Plant - Muchlisin Muchlisin; Budi Utomo Kukuh Widodo (Institut Teknologi Sepuluh Nopember, 2019)
A condenser is one of the main equipment in a Combined Cycle Power Plant (CCPP) cooling system which has a great influence on steam turbine output and thermal efficiency of the whole power plant as well. The objective of this study is to analyze the effect of increase in condenser pressures on the heat rate and electricity production costs. The primary data is acquired from the DCS. These data are then compared to those of the best performance operating data. The differences of these two data of 23 parameters, are then integrated with the impact factor to gain the heat rate loss. Based on the heat rate loss, then the cost of electricity production is established accordingly. The study concludes that the increase of condenser pressure from 2.41 inHgA to 2.82 inHgA results in increase of plant heat rate 19.55 kcal/kWh. The 5 great parameters to contribute to this loss are: HP and LP steam flows, condenser pressure, stack temperatures of HRSG 1.3 and 1.2. Meanwhile, the cost of production rises up from 751 IDR/kWh to 805 IDR/kWh